Survey Self Regulated Learing pada Maharah Kalam Dimasa Pandemi - Rahma; Nurul Wahdah; Nur Fuadi Rahman (MUMTAZA Journal of Arabic Teaching, Arabic Linguistic and Literature, 2023)
This study aims to determine the level of learning independence in Maharah Kalam during a pandemic. In this study, researchers used a quantitative approach to survey research. A total of 89 respondents participated in this study. The data collection technique uses a questionnaire instrument with descriptive statistical data analysis techniques using averages. Based on the results of the research, it is known that: 1) the learning motivation of Maharah Kalam students during the pandemic was included in the high category with an average of 4.21; 2) Student learning behavior in Maharah Kalam learning during the pandemic was in the high category with an average of 4.08; 3) Students' metacognition in Maharah Kalam learning during the pandemic was in the high category with an average of 4.10. Overall, Maharah Kalam's level of Self Regulated Learning  (SRL) during the pandemic was in the high category with an average of 4.14 Keyword: Self Regulated Learning, Maharah Kalam, Pandemic.   Abstrak Penelitian ini bertujuan  untuk mengetahui tingkat Self Regulated Learning  (SRL)maharah kalam di masa pandemi. Dalam penelitian ini, peneliti menggunakan pendekatan kuantitatif dengan jenis penelitian survei. Sebanyak 89 responden berpartisipasi dalam penelitian ini. Teknik pengumpulan data menggunakan instrumen angket dengan teknik analisis data statistik deskriptif dengan menggunakan rata-rata. Berdasarkan hasil penelitian diketahui bahwa: 1) Motivasi belajar maharah kalam bagi mahasiswa di masa pandemi berkategori tinggi dengan rata-rata sebesar 4.21; 2)  Perilaku belajar mahasiswa dalam belajar maharah kalam di masa pandemi berkategori tinggi dengan rata-rata sebesar 4.08; 3) Metakognisi mahasiswa dalam belajar maharah kalam di masa pandemi berkategori tinggi dengan rata-rata sebesar 4.10. Secara keseluruhan  tingkat Self Regulated Learning  (SRL) maharah kalam di masa pandemi berkategori tinggi dengan rata-rata sebesar 4.14. Kata Kunci: Self Regulated Learning, Maharah Kalam, Pandemi.